The codes guidebook for interiors - Kennon, Katherine E.; Harmon, Sharon Koomen 1964- (Hoboken, New Jersey John Wiley & Sons, 2018)
Interior codes and standards reference of choice for designers and architects, updated and revised. Completely revised and updated, the seventh edition of The Codes Guidebook to Interiors is the only book devoted exclusively to codes that are applicable to interior designers. The guide features jargon-free explanations of all the codes and standards that are relevant to designers and architects, including performance codes, building and finish standards, energy codes, and ADA standards. In addition, the dozens of examples and a greatly enhanced with a set of illustrations, including floor plans, that clearly show how codes apply to real-world project.--Provided by publisher.
Includes index.
Earlier editions were under Harmon, Sharon K.
Keywords: Building laws -- United States; Buildings -- Specifications -- United States; Interior architecture -- Specifications -- United States